Gadara, Jordanien. Der ‚Gadara/Umm Qays Hinterland Survey‘. Die Arbeiten im Herbst 2019 - Rokitta-Krumnow, Dörte (e-Forschungsberichte des DAI, 2020)
Since 2010, the German Archaeological Institute, Orient Department, Damascus Branch, conducts a hinterland survey around the ancient city of Gadara in north-western Jordan. The steep and sloping terrain with its mostly deflated surfaces is on the one hand difficult to survey and on the other hand only rarely allows for finding in situ findspots. Actual sites or findspots almost exclusively consist of ancient quarries, water channels and rock shelters which are still in use. Nevertheless, the region is rich in lithic material of different time periods, but with a dominant evidence of Middle-Paleolithic material. In addition, pottery and glass of predominantly/especially Roman origin and pottery of Islamic periods are evidence for the continuously settled area.